Perancangan Manajemen Bandwidth Pada Jaringan Internet Menggunakan Hierarchical Teken Bucket (HTB) Di SMAN 12 Pekanbaru - Siregar, Vivi Devina; Marpaung, Noveri Lysbetti; Hutabarat, Sakti; Ervianto, Edy; Nurhalim, Nurhalim; Amri, Rahyul (LPPM Universitas Potensi Utama, 2025)
In today’s digital era, the availability of a stable and efficient internet network is a crucial need to support teaching and learning activities in educational environments. SMAN 12 Pekanbaru, as one of the schools implementing technology-based learning, is experiencing issues related to uneven bandwidth distribution, especially during peak usage hours. This often disrupts access to essential school services such as online exams and digital learning platforms. This study aims to design a bandwidth management system using the Hierarchical Token Bucket (HTB) method with the Mikrotik RB750Gr3 device to optimize internet bandwidth distribution at SMAN 12 Pekanbaru. The methodology involves analyzing the existing network issues, designing a new network topology, configuring HTB, measuring Quality of Service (QoS) parameters, and conducting data analysis. he results show an improvement in network performance, with more stable average throughput, reduced delay and jitter, and minimal packet loss during peak hours. The implementation of the HTB method proves effective in providing better control over bandwidth allocation based on user and service priorities, thereby supporting more efficient and effective digital-based teaching and learning activities.